Mechanism of action of Caveolae and its impact pathways - Xiu Du; Lin Xu; Su Cheng; Yan-ru Wang; Ming-hai Shao (Editorial Department of Journal of Clinical Nephrology, 2024)
As an important component of transcellular pathway, Caveolae enables the transcellular transport of substances without disrupting cellular homeostasis. In kidney, albumin crosses glomerular filtration barrier (GFB) via Caveolae. Transcellular transport of albumin plays a crucial role in the pathology of proteinuria. Thus the importance of Caveolae cannot be overstated. However, the acting mechanism of Caveolae affecting transcellular albumin transport in kidney and their signaling pathways have remained largely elusive. This review summarized the latest studies on the regulation of Caveolae affecting transcellular albumin transport. Thus elucidating the relevant mechanisms of action and understanding the pathways of influence may provide potential therapeutic targets in the prevention and alleviation of proteinuria